Review of Dave Tompkins. 2010. How to Wreck a Nice Beach. Chicago and Brooklyn: Stop Smiling/Melville House. Steve Goodman. 2010. Sonic Warfare. Cambridge, MA, and London: MIT Press. - Marshall, Wayne (Current Musicology, 2010)
At first glance, Dave Tompkins’s How to Wreck a Nice Beach and Steve Goodman’s Sonic Warfare would seem to have a lot in common. Both books feature the creative “abuse” of military technology by musicians, an abiding appreciation for Afro-sonic futurisms, prose styles at times so idiosyncratic as to be arcane, and brief but key appearances by William Burroughs. Both also depart, whether implicitly or explicitly, from the general preoccupation with form still guiding the musicological status quo. This formalist bias affects both how we tend to listen as well as how we write. Instead, these books, each in their own way, propose novel and provocative modes of grappling with and making sense (or nonsense) of music and sound.